Navigating Hydrogen Horizons - Mapping the Technological Innovation System of Mid Sweden Hydrogen Valley A case study in collaboration with CIT Renergy - Banjac, Tom; Sörum, Melvin (My University)
The transition towards a sustainable energy future necessitates the adoption of fossil-free technologies, with hydrogen emerging as a pivotal element in achieving climate neutrality. Hydrogen valleys – a geographical area where several hydrogen applications are combined together into an integrated hydrogen ecosystem, are identified by the European Commission as important enablers for transitioning into a full-scale hydrogen economy. This master thesis investigates Mid Sweden Hydrogen Valley (MSHV) – a hydrogen valley in early formation in Sweden, using a Technological Innovation System (TIS) framework. Due to the novelty of hydrogen valleys, few studies have analyzed hydrogen valleys using system level frameworks like TIS – which could provide valuable insights regarding how a hydrogen valley should be developed. By employing a qualitative case study approach, data was collected through 21 interviews with members of MSHV. Key findings reveal that a hydrogen valley is a complex system, including diverse networks of actors both in the main hydrogen value chain, through supporting value chains, and other influences such as grant providers and authorities. The findings also reveal that MSHV performs relatively well based on the appraisal of its seven functions. Still, five challenges (labeled blocking mechanisms) are identified that prevent the hydrogen valley from moving smoothly from a formative phase into a growth phase. These challenges are addressed by proposing five recommendations for policymakers and three recommendations for managers, which emphasize the need for collaboration, improved economics, and political support. Finally, the study concludes by suggesting directions for future research.
Keywords: Hydrogen Valley; Technological Innovation System; Fossil-free Hydrogen; Sociotechnical Transformation; Sustainable Transformation